Remission of Prediabetes and Diabetes - Selim, Shahjada (Bangladesh Journal of Medicine, 2024)
The concept of type 2 diabetes remission is evolving rapidly, and gaining wide public and professional interest, following the demonstration that with substantial intentional weight loss almost nine in ten people with type 2 diabetes can reduce their HbA1c level below the diagnostic criterion (48 mmol/mol [6.5%]) without glucoselowering medications, and improve all features of the metabolic syndrome. Pursuing nomoglycaemia with older drugs was dangerous because of the risk of side effects and hypoglycemia, so the conventional treatment target was an HbA1c concentration of 53 mmol/mol (7%), meaning that diabetes was still present and allowing disease progression. Newer agents may achieve a normal HbA1c safely and, by analogy with treatments that send cancers or inflammatory diseases into remission, this might also be considered remission. Remission of prediabetes and diabetes is possible, especially with lifestyle changes and, in some cases, medical intervention. Here’s a breakdown: Adopting a healthy diet rich in fruits, vegetables, whole grains, lean proteins, and healthy fats while limiting processed foods, sugary drinks, and refined carbohydrates can help manage blood sugar levels and promote weight loss. Regular physical activity, such as brisk walking, cycling, or swimming, can improve insulin sensitivity, aid in weight loss, and help control blood sugar levels. Losing excess weight, even a modest amount, can significantly improve insulin sensitivity and reduce the risk of developing type 2 diabetes or help manage the condition if already diagnosed. Techniques such as mindfulness, meditation, yoga, or deep breathing exercises can help reduce stress levels, which can impact blood sugar control. Smoking can contribute to insulin resistance and increase the risk of complications related to diabetes. Quitting smoking can improve overall health outcomes. In some cases, medications like metformin may be prescribed to help lower blood sugar levels and improve insulin sensitivity. Other medications or insulin therapy may be necessary depending on individual circumstances. For severely obese individuals with diabetes, bariatric surgery may be recommended. This surgery can lead to significant weight loss and, in many cases, remission of type 2 diabetes. Regular monitoring of blood sugar levels, A1C levels, and other health parameters is crucial for managing prediabetes and diabetes effectively. It allows for adjustments to treatment plans as needed. Continued support from healthcare providers, including education on self-management strategies, nutrition counseling, and access to support groups, can be instrumental in achieving and maintaining remission. It’s important to note that while remission is possible, diabetes is a chronic condition that requires ongoing management. Even if someone achieves remission, they still need to maintain healthy lifestyle habits and regular monitoring to prevent relapse. Additionally, individual responses to treatment can vary, so what works for one person may not work for another. Always consult with a healthcare professional for personalized advice and guidance. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 149